2007
DOI: 10.1016/j.brainres.2007.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection by neuregulin-1 in a rat model of permanent focal cerebral ischemia

Abstract: Neuregulin-1 (NRG-1) is a growth factor with potent neuroprotective capacity in ischemic stroke. We recently showed that NRG-1 reduced neuronal death following transient middle cerebral artery occlusion (tMCAO) by up to 90% with an extended therapeutic window. Here, we examined the neuroprotective potential of NRG-1 using a permanent MCAO ischemia (pMCAO) rat model. NRG-1 reduced infarction in pMCAO by 50% when administered prior to ischemia. We previously demonstrated using gene expression profiling that pMCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 41 publications
4
63
0
Order By: Relevance
“…NRG-induced ErbB signaling plays an important role in the development and homeostasis of the nervous system (2,23,24), and may even be a candidate for neuroprotection (25,26). Its role in the developing lung is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…NRG-induced ErbB signaling plays an important role in the development and homeostasis of the nervous system (2,23,24), and may even be a candidate for neuroprotection (25,26). Its role in the developing lung is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Because blood flow increases extracellular glutamate levels to concentrations that are lethal to neurons, many studies target glutamate signaling transmission as a treatment for stroke. A large number of preclinical studies have demonstrated a beneficial effect of NMDA receptor antagonist administration to treat and/or prevent ischemic strokerelated neurodegeneration [101][102][103][104][105], but none of these therapeutic strategies have demonstrated success in the clinic [106,107]. Inappropriate design, incorrect dosing concentrations, improper selection of drugs, and difficulties in treating patients within a given period of time immediately after the ischemic insult certainly have limited the success of these treatment.…”
Section: Strokementioning
confidence: 99%
“…Rats were anesthetized with an intraperitoneal injection of chloral hydrate (300 mg/kg). Permanent middle cerebral artery occlusion (pMCAO) was induced using the suture occlusion model as described previously [17]. Briefly, the right common carotid artery (CCA) and external carotid artery (ECA) were carefully exposed through a ventral midline neck incision.…”
Section: Animal Modelmentioning
confidence: 99%